Evaluasi Tingkat Kinerja Lalu Lintas dan Aksesibilitas Jalan di Sekitar Alun-Alun Kebumen Pasca Revitalisasi Kawasan - Zulkarnaen, Afrizal (Jurnal Kridatama Sains dan Teknologi, 2025)
The revitalization of Alun-Alun Kebumen, a central public open space, has brought significant changes to traffic characteristics and road accessibility in its surrounding areas. Increased community activities following the revitalization led to a 12.4% rise in traffic volume during peak hours, changes in vehicular movement patterns, and localized congestion at key junctions. This study aims to evaluate post-revitalization traffic performance and network accessibility around the Alun-Alun Kebumen area. The methodology involved direct surveys of traffic volume, vehicle speed measurements, delay observations, and documentation of current road conditions. Data were analyzed using the Indonesian Highway Capacity Manual (Indonesia, 1997)) focusing on road capacity, volume-to-capacity ratio (V/C or Degree of Saturation), and Level of Service (LOS). The findings reveal an increase in DS on Jalan Kusuma, reaching 0.89 (LOS D), and a shift to one-way traffic systems has resulted in less direct connectivity between road segments. While the revitalization has improved pedestrian comfort and urban aesthetics, it has also imposed pressure on motorized traffic performance. Policy recommendations include reconfiguring traffic circulation and enhancing transport mode integration to ensure the long-term functionality of Kebumen's urban core